RATIONALE FOR PREVENTION OF CARDIO-CEREBRAL COMPLICATIONS IN THE METABOLIC SYNDROME BASED ON MATHEMATICAL FORECASTING TECHNIQUES - S. V. Chernavskii; A. N. Fursov; N. P. Potekhin; V. N. Yakovlev (Klinicist, 2014)
Objective — to study prevention of cardio-cerebral complications of metabolic syndrome on the basis of mathematical methods of forecasting. Subjects and methods. A discriminant analysis of clinical and instrumental data of patients with MS. Results of this study allow the early (prenosological) stages of the metabolic syndrome using the linear discriminant equations to predict the development of myocardial infarction up to 89.3 %, stroke — up to 87.8 %. Conclusion. The diagnostic and treatment algorithms developed based on the stratification of cardiovascular risk index, allow us to give sound recommendations for targeted prevention of cardio-cerebral complications.